A COMPARATIVE STUDY REGARDING THE BODY'S REACTION TO EFFORT DURING HIKING TOURS, ACCORDING TO THE DIFFICULTY OF THE ROUTE, TRAINING LEVEL, AND AGE - Rata Bogdan Constantin; Dragoi Cristian Corneliu (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
Our research aims to do a comparative study that involves the body's reaction to effort during hiking tours that are different from the point of view of their difficulty (length, duration and inclination). Our experimental group comprised students from the FMSHS, under the coordination of a teacher specialized in Practical Courses in Tourism Activities. The training level and the age of the subjects differed. To collect the necessary data, we used pulse-testers, recording the heart rate during different moments of the tours, in the beginning and at the end of the breaks. The results we recorded have helped us to compare the individual reactions to effort and to draw several conclusions.